Optimizing graphene content in a NiSe/graphene nanohybrid counter electrode to enhance the photovoltaic performance of dye-sensitized solar cells. Issue 38 (25th September 2019) - Murugadoss, Vignesh; Lin, Jing; Liu, Hu; Mai, Xianmin; Ding, Tao; Guo, Zhanhu; Angaiah, Subramania
Abstract : Optimizing the graphene mass ratio in NiSe/GN counter electrodes enabled the fabrication of high performance dye-sensitized solar cells with excellent electrocatalytic activity and chemical stability. Abstract : Nickel selenide (NiSe) nanoparticles were grown on graphene nanosheets (GN) with different mass ratios to obtain their corresponding NiSe/GN x ( x = 0.25 to 1.00) nanohybrids by a facile in situ hydrothermal process to integrate the advantages of the high specific surface area of graphene and the homogeneously immobilized catalytic sites of NiSe. The nanohybrid with a mass ratio of 1 : 0.50 ( i.e., NiSe/GN0.50 ) exhibited higher electrocatalytic activity and electrolyte diffusion. Thus, NiSe/GN0.50 exhibited an improved photo-conversion efficiency (PCE) of 12% ( η = 8.62%) compared to a standard Pt ( η = 7.68%)-based dye-sensitized solar cell (DSSC). This improved PCE mainly originated from the catalytic ability of NiSe and the multiple interfacial electron transfer pathways of graphene, resulting in enhanced charge transfer and fast tri-iodide reduction kinetics at the counter electrode/electrolyte interface. The results obtained from the cyclic voltammetry (CV), electrochemical AC-impedance (EIS) and Tafel polarization studies validated the synergistic effects of NiSe and GN and the high potential of this nanohybrid as an efficient counter electrode (CE) for DSSCs.